Chemical effects of high‐resolution YbLγ4 emission spectra: a possible probe for chemical analysis. (23rd July 2013) - Hayashi, Hisashi; Kanai, Noriko; Kawamura, Naomi; Matsuda, Yasuhiro H.; Kuga, Kentaro; Nakatsuji, Satoru; Yamashita, Tetsuro; Ohara, Shigeo
<x xml:space="preserve">Abstract</x> An 'eccentric' X‐ray emission, YbLγ4, was measured for Yb metal, Yb2O3, YbF3, β‐YbAlB4, YbNi3Al9, and YbNi3Ga9 with a resolution of ~0.9 eV. Peak splitting of the YbLγ4 line was observed in all the recorded spectra and was attributed to the two components originating from the LS coupling of the Yb5p hole, the Yb5p1/2 (LIOII: Lγ4′) and Yb5p3/2 components (LIOIII: Lγ4). The spectra were substantially different depending on the chemical environment of Yb. The position of the Lγ4 + Lγ4′ band shifts depending on the valence of Yb (v): ~4.4 eV from divalent to trivalent. The Lγ4 + Lγ4′ spectra of the mixed valence intermetallics, i.e. YbNi3Ga9 (v = 2.59) and β‐YbAlB4 (v = 2.75), were fairly well reproduced by averaging the spectra of divalent Yb and trivalent YbNi3Al9, which suggests the possibility of using the YbLγ4 emission for determining the valence of Yb intermetallics. In trivalent Yb compounds, the relative intensity of Lγ4 compared with that of Lγ4′, as well as the appearance of a high‐energy satellite, was found to be influenced by the ligands around the Yb ions. With the aid of preliminary atomic multiplet and band structure calculations, the differences in the valence band structure and resultant screening effects on the OII, III−1 states were determined to be the possible causes for the observed ligand dependence. © 2013 The Authors. X‐ray spectrometry published by John Wiley & Sons, Ltd.